Observation of ionic conductivity on PUA-TBAI-I2 gel polymer electrolyte - Chai, K. L.; Aung, Min Min; Noor, I. M.; Lim, H. N; Abdullah, L. C. (Springer Nature, 2022)
Jatropha oil-based polyurethane acylate gel polymer electrolyte was mixed with different concentrations of tetrabutylammonium iodide salt (TBAI). The temperature dependences of ionic conductivity, dielectric modulus and relaxation time were studied in the range of 298 to 393 K. The highest ionic conductivity of (1.88 ± 0.020) × 10–4 Scm−1 at 298 K was achieved when the gel contained 30 wt% of TBAI and 2.06 wt% of I2. Furthermore, the study found that conductivity-temperature dependence followed the Vogel-Tammann Fulcher equation. From that, it could be clearly observed that 30 wt% TBAI indicated the lowest activation energy of 6.947 kJ mol−1. By using the fitting method on the Nyquist plot, the number density, mobility and diffusion coefficient of the charge carrier were determined. The charge properties were analysed using the dielectric permittivity, modulus and dissipation factor. Apart from this, the stoke drag and capacitance were determined.